IMPLEMENTASI PEMBIASAAN KEAGAMAAN DALAM MEMBENTUK KARAKTER SISWA KELAS V DI SDIT NURUL IMAM - Ismayuni Ismayuni; Dede Ajeng Arini; Agus Jaenal (Prodi PGMI STAI Sabili Bandung, 2026)
This study aims to determine the implementation of religious habituation in shaping the character of fifth-grade students at SDIT Nurul Imam. This study employed a descriptive qualitative approach with data collection techniques consisting of observation, interviews, and documentation. The research subjects included Islamic Education teachers, homeroom teachers, and fifth-grade students of SDIT Nurul Imam. The results showed that the religious habituation activities implemented at SDIT Nurul Imam included morning murojaah, congregational dhuha prayer, reciting prayers before and after learning activities, chanting Asmaul Husna, Friday charity, hadith memorization, and khotmil Qur’an activities. These activities were carried out routinely and systematically, enabling students to internalize religious values in their daily lives. The implementation of religious habituation had a positive influence on students’ character development, particularly in the aspects of discipline, responsibility, honesty, and politeness. Based on the research findings involving 25 students, 84% demonstrated disciplined behavior, 80% showed good responsibility, 88% displayed honesty, and 92% exhibited polite attitudes. Supporting factors in implementing religious habituation included support from the school and foundation, teachers’ role modeling, an Islamic school environment, adequate facilities and infrastructure, as well as cooperation between the school and parents. Meanwhile, inhibiting factors included the lack of discipline among some students, limited religious habituation within the family environment, and the negative influence of technology and the surrounding environment. Therefore, the implementation of religious habituation at SDIT Nurul Imam proved effective in shaping the religious character of fifth-grade students.